Polygonum multiflorum-Induced Liver Injury: Clinical Characteristics, Risk Factors, Material Basis, Action Mechanism and Current Challenges - Liu, Yi; Wang, Wenping; Sun, Mingyi; Ma, Baorui; Pang, Linnuo; Du, Yuanyuan; Dong, Xiaoxv; Yin, Xingbin; Ni, Jian (Frontiers in Pharmacology, 2019)
Polygonum multiflorum Thunb. (PM), called Heshouwu in China, is a popular Chinese medicine in clinical practice. In recent years, reports on clinical adverse reactions of Raw Radix Polygonum multiflorum (RPM) and Polygonum multiflorum Praeparata (PMP) have been on the increase, especially with respect to liver injury. However, the components of PM responsible for the reported hepatotoxic effects have not yet been identified. Moreover, many of the reports are contradictory, while studies on the mechanism involved in PM-induced liver damage are not comprehensive. This study was aimed at reviewing the status of research on liver injury due to PM, including clinical characteristics, risk factors, material basis research and mechanism of action, with a view to understanding PM-induced hepatotoxicity, and taking reasonable and effective measures to prevent it. In short, quality control is still one of the major safety problems in TCM drug safety concerns. The model of safety monitoring and risk management of PM drugs is not yet developed. Indeed, the characteristics and risk factors associated with PM require both proper understanding and control of the risk by strengthening standardization of clinical applications, basic science research, quality control in manufacturing, active monitoring methodology and enhancement of international communication and cooperation. Measures should also be encouraged and implemented to promote healthy development of the TCM industry.